(untitled) (Advances in Applied Biological Research, 2026)
Background: The obvious increase in mobile phone base stations in Iraq after the year 2003 has raised worries about potential nonspecific health symptoms affected by electromagnetic radiation produced. Studies on this issue in Iraq were scarce. Objective of the study: To identify the possible nonspecific health problems among adult inhabitants who lived for five years or more at a distance of up to 300 meters from mobile phone base stations and towers compared to those who lived far away from cell phone towers (500 meters and more). Methods: A cross sectional descriptive study was conducted in Hilla city, Babylon province, during the period from November 2017 through February 2018. A non-probability (purposive sample) was selected from populations living in AL-Hilla urban regions for more than five years close to four randomly selected base station towers and those who lived in areas more than 500 meters from the same cell towers. A convenience sample constituted 278 adults aged 18 years and above of both sexes who were investigated after obtaining their verbal consent and who had completed a pretested questionnaire that focused on the subjective symptoms they suffered from via in-depth face-to-face interviews. Results: The findings of the current study revealed a statistically significant increase in ill-health effects (prevalence of nonspecific symptoms) <0.05 among those living in the locality <300 meters from mobile telephone base stations compared to those who lived far away from the mobile phone stations >500 meters. The strongest associations (<0.01) were fatigue, headache, sleeping disorders, difficulty in concentration, and dizziness. The male-to-female ratio in this study was 1.5:1. The social problems related to this health issue included that only one in five of the participants mentioned that they were informed before setting the stations near their houses, and 75% of inhabitants near the stations reported conflicts with the owner of the building where the cell phone tower was placed. Conclusion: The study found significant health-related nonspecific symptoms (headache, fatigue, and sleep disturbance) among adults living close to mobile telephone base stations compared to those who lived far away. It is sensible that mobile telephone base stations be located at least 500 meters from the houses of inhabitants.